2019
DOI: 10.3390/nu11092085
|View full text |Cite
|
Sign up to set email alerts
|

Extra Virgin Olive Oil: Lesson from Nutrigenomics

Abstract: Extra virgin olive oil (EVOO) consumption has a beneficial effect on human health, especially for prevention of cardiovascular disease and metabolic disorders. Here we underscore the peculiar importance of specific cultivars used for EVOO production since biodiversity among cultivars in terms of fatty acids and polyphenols content could differently impact on the metabolic homeostasis. In this respect, the nutrigenomic approach could be very useful to fully dissect the pathways modulated by different EVOO culti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(70 citation statements)
references
References 114 publications
(124 reference statements)
1
62
1
6
Order By: Relevance
“…A large number of studies have clearly established that the Mediterranean (Med) diet is the cornerstone of CVD prevention. In Med diet, virgin olive oil (VOO) and extra-virgin olive oil (EVOO) are the major sources of fat and active phenolic compounds, responsible for the minor mortality and morbidity noted in people on such a diet [ 1 , 6 , 7 ]. Besides high levels of monounsaturated fatty acids (MUFA), VOO and mostly EVOO contain several minor phenolic components with biological properties, such as the ability of modulating biomarkers involved in pathways implicated in the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of studies have clearly established that the Mediterranean (Med) diet is the cornerstone of CVD prevention. In Med diet, virgin olive oil (VOO) and extra-virgin olive oil (EVOO) are the major sources of fat and active phenolic compounds, responsible for the minor mortality and morbidity noted in people on such a diet [ 1 , 6 , 7 ]. Besides high levels of monounsaturated fatty acids (MUFA), VOO and mostly EVOO contain several minor phenolic components with biological properties, such as the ability of modulating biomarkers involved in pathways implicated in the development of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, the European Food Safety Authority (EFSA) in 2011 has approved a health claim stating that the dietary intake of VOO's polyphenols is able to protect blood lipids from oxidative damage. However, in order this claim to be valid, 5 mg/day of hydroxytyrosol and its derivatives should be consumed (Commission Regulation, EU, 432/2012) [16,[42][43][44].…”
Section: Oxidative Stress and Inflammationmentioning
confidence: 99%
“…Foods rich in unsaturated fatty acids, like extra virgin olive oil, even if correlated to benefic effects in different pathological conditions [118][119][120], seem to produce negative effects on iron absorption. A study conducted on rats showed that unsaturated and polyunsaturated fatty acids influence negatively iron bioavailability, its absorption, and its utilization by the animals when compared to saturated fatty acids [121].…”
Section: Nutritional Sources That Hinder Iron Absorptionmentioning
confidence: 99%